Study on the relationship between plasma Gd-IgA1 concentration and disease severity in IgA nephropathy and its production mechanism - DAI Qin; MIAO Yi; WANG Wei-ming (Linchuang shenzangbing zazhi)
Objective To determine the relationship between the level of plasma Gd-IgA1(galactose-deficient IgA1) and disease severity in IgA nephropathy(IgAN) patients, and to explore the possible mechanism of abnormal glycosylation of IgA1 from the perspective of epigeneticsMethods In this study, 59 patients with primary IgA nephropathy and 30 healthy controls were included. The levels of plasma IgA1 and Gd-IgA1 were detected by ELISA, and the correlation between the levels of Gd-IgA1, proteinuria and estimated glomerular filtration rate(eGFR) was analyzed. The mRNA expression level of glycosylase was detected by real time-PCR, and the acetylation degree of histones H3 and H4 in the promoter region of the glycosylase gene was detected by chromatin immunoprecipitation(CHIP).Results(1) The concentrations of IgA1 and Gd-IgA1 in the IgAN group were significantly higher than those in the control group(P<0.01), and the concentration of Gd-IgA1 in the IgAN group was positively correlated with 24-hour urinary protein(r=0.479, P<0.01).(2) The mRNA expression levels of C1 GALT1 and ST6 GALNAC2 in IgA nephropathy group were(0.28±0.06) times and(2.88±0.60) times those in the control group(P<0.01).(3) The acetylation degrees of H3 in the promoter region of C1 GALT1 and ST6 GALNAC2 genes in the IgAN group were(0.43±0.20) times and(3.42±1.32) times(P<0.05) those in te control group; and the acetylation degrees of H4 were(0.62±0.11) times and(2.07±0.29) times those in the control group, respectively(P<0.01). Conclusion The higher the concentration of Gd-IgA1 in the plasma of IgA nephropathy patients, the more the amount of urine protein; the increased level of Gd-IgA1 may be related to the decreased degree of acetylation of histones H3 and H4 in the promoter region of C1 GALT1 gene and the increased degree of acetylation of histones H3 and H4 in the promoter region of ST6 GALNAC2 gene.